2017
DOI: 10.5897/jpbcs2017.0641
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of introduced Korean rice genotypes for resistance to rice blast in Uganda

Abstract: Rice blast caused by Magnaporthe grisea is an economically important disease which distributed in most rice growing areas of the world. Yield losses up to 100% are attributed to the blast disease in different rice growing regions of Uganda. In order to combat this disease screening of forty-six introduced Korean rice accessions and two checks IR-64 (resistant) and NERICA-1 (susceptible) were done in a 6 by 8 alpha lattice design in two replications under natural infestation in field conditions, and three repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…The genotypes differed in their reaction to blast based on the different silicon concentrations indicating a difference in performance of the rice genotypes under the different silicon concentrations. Similar findings were reported by [8,20] who screened rice genotypes against rice blast. These variations were attributed to different genetic constituents and the amount of silicon added to the soil.…”
Section: Discussionsupporting
confidence: 88%
“…The genotypes differed in their reaction to blast based on the different silicon concentrations indicating a difference in performance of the rice genotypes under the different silicon concentrations. Similar findings were reported by [8,20] who screened rice genotypes against rice blast. These variations were attributed to different genetic constituents and the amount of silicon added to the soil.…”
Section: Discussionsupporting
confidence: 88%
“…Initial infection and higher disease severity occurred on the local variety and SUPERICA 1, but apart from NERICA 6, NERICA 10 and the NamChe varieties displayed higher disease resistance. The 2017B season characterized by high relative humidity, rainfall and plant vegetative growth experienced high disease especially on the fertilizer treated plots agreeing with the fact that higher Nitrogen fertilizer application favours rice blast epidemics [6]. These results implies the higher rainfall created conducive environments for the pathogen multiplication and survival, moreover, disease severity was higher on the lower leaves in the high inoculum prone, cool and humid environment that was less exposed to sunshine [23].…”
Section: Discussionsupporting
confidence: 68%
“…However, the existence of conidia in the environment season after season, and the likely presence of the pathogen in seed [25], may have generated the high inoculum that resulted in severe disease epidemics that spread to improved varieties. Rice blast can cause up to 90% yield loss on susceptible varieties, but germplasm evaluation studies have identified externally introduced genotypes with high to moderate resistance to M. grisea races existing in Uganda that can be used to improve the most preferred varieties with durable blast resistance gene pyramids [6]. Besides NamChe 3, which has been previously reported as a potential source of disease resistance [12], NERICA 10 consistently displayed higher resistance to rice blast.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanisms of crop tolerance to drought can be grouped into three categories: escape, avoidance, and tolerance. Escape is the plant's ability to complete its life cycle before experiencing extreme drought through flowering and bearing early fruits (Abdullah et al, 2010). Avoidance is the plant's ability to maintain higher potential cell water, aligned with the increasing drought, so that the turgidity cell remains higher by reducing water loss or increasing water absorption (Tubur et al, 2012), while tolerance is the ability of a species or a variety to stay alive and keep performing its function despite the stress (Man et al, 2011).…”
Section: Introductionmentioning
confidence: 99%